Hemi-transseptal Approach for Pituitary Surgery: A Follow-Up Study - Fnais, Naif; Maio, Salvatore Di; Edionwe, Susan; Zeitouni, Anthony; Sirhan, Denis; Valdes, Constanza J.; Tewfik, Marc A. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives The hemi-transseptal (Hemi-T) approach was developed to overcome the potential drawbacks of the nasoseptal flap (NSF) in endoscopic endonasal transsphenoidal skull base surgery. In this study, we describe further refinements on the Hemi-T approach, and report long-term outcomes as compared with traditional methods of skull base reconstruction.Design A retrospective case-control study.Setting Montreal Neurological Institute and Jewish General Hospital, Montreal, Canada.Participants Patients who underwent endoscopic endonasal transsphenoidal approach to skull base pathology.Main Outcome Measures Operative time, CSF rhinorrhea, and postoperative nasal morbidity.Results A total of 105 patients underwent the Hemi-T approach versus 40 controls. Operative time was shorter using the Hemi-T technique (180.51 ± 56.9 vs. 202.9 ± 62 minutes; p = 0.048). The rates of nasal morbidity (septal perforation [5/102 vs. 6/37; p = 0.029] and mucosal adhesion [11/102 vs. 10/39 p = 0.027]), fascia lata harvest (21/100 vs. 18/39; p = 0.0028), and postoperative CSF leak rates (7/100 vs. 9/38; p = 0.006) were lower in the Hemi-T group.Conclusion Advantages of the Hemi-T approach over traditional exposure techniques include preservation of the nasal vascular pedicle, shorter operative time, reduced fascia lata harvest rates, and decreased nasal morbidity.
Keywords: skull base; pituitary surgery; endoscopic endonasal; nasoseptal flap